A novel RBMX‐TFE3 gene fusion in a highly aggressive pediatric renal perivascular epithelioid cell tumor. Issue 1 (2nd September 2019) - Argani, Pedram; Zhang, Lei; Sung, Yun‐Shao; White, Marissa J.; Miller, Karin; Hopkins, Mark; Small, Donald; Pratilas, Christine A.; Swanson, David; Dickson, Brendan; Antonescu, Cristina R.
Abstract: We report an Xp11 translocation perivascular epithelioid cell tumor (PEComa) with a novel RBMX‐TFE3 gene fusion, resulting from a paracentric X chromosome inversion, inv(X)(p11;q26). The neoplasm occurred in an otherwise healthy 12‐year‐old boy who presented with a large left renal mass with extension into the inferior vena cava. The patient was found to have multiple pulmonary metastases at diagnosis and died of disease 3 months later. The morphology (epithelioid clear cells with alveolar and nested architecture) and immunophenotype (TFE3 and HMB45 strongly positive; actin, desmin, and PAX8 negative) was typical of an Xp11 translocation PEComa; however, TFE3 rearrangement was initially not detected by routine TFE3 break‐apart fluorescence in situ hybridization (FISH). Further RNA sequencing revealed a novel RBMX‐TFE3 gene fusion, which was subsequently confirmed by fusion assay FISH, using custom design RBMX and TFE3 come‐together probes. This report describes a novel TFE3 gene fusion partner, RBMX, in a pediatric renal PEComa patient associated with a fulminant clinical course. As documented in other intrachromosomal Xp11 . 2 inversions, such as fusions with NONO, RBM10, or GRIPAP1 genes, the TFE3 break‐apart might be below the FISH resolution, resulting in a false negative result.